Mesoglycan: Clinical Evidences for Use in Vascular Diseases - Antonella Tufano; Claudia Arturo; Ernesto Cimino; Matteo Nicola Dario Di Minno; Mirko Di Capua; Anna Maria Cerbone; Giovanni Di Minno (International Journal of Vascular Medicine)
Vascular glycosaminoglycans (GAG) are essential components of the endothelium and vessel wall and have been shown to be involved in several biologic functions. Mesoglycan, a natural GAG preparation, is a polysaccharide complex rich in sulphur radicals with strong negative electric charge. It is extracted from porcine intestinal mucosa and is composed of heparan sulfate, dermatan sulfate, electrophoretically slow-moving heparin, and variable and minimal quantities of chondroitin sulfate. Data on antithrombotic and profibrinolytic activities of the drug show that mesoglycan, although not indicated in the treatment of acute arterial or venous thrombosis because of the low antithrombotic effect, may be useful in the management of vascular diseases, when combined with antithrombotics in the case of disease of cerebral vasculature, and with antithrombotics and vasodilator drugs in the case of chronic peripheral arterial disease. The protective effect of mesoglycan in patients with venous thrombosis and the absence of side effects, support the use of GAG in patients with chronic venous insufficiency and persistent venous ulcers, in association with compression therapy (zinc bandages, multiple layer bandages, etc.), elastic compression stockings, and local care, and in the prevention of recurrences in patients with previous DVT following the standard course of oral anticoagulation treatment.